Some reproductive characters of the fantail goldfish Carassius auratus auratus females from rearing ponds in Basrah, Southern Iraq. - Najim, Salah M.; Al-Mudhaffar, Raja A.A.; Jassim, Furat K. (Iraqi Journal of Aquaculture, 2022)
This study was carried out to determine some reproductive characteristics of the fantail goldfish Carassius auratus auratus females (standard length 69-224 mm. and total weight 21.1- 255.35 g.) from rearing ponds in Basrah province, Southern Iraq. Standard length, total weight, gonad weight, absolute fecundity, relative fecundity, gonadosomatic index (GSI) and egg diameter were determined from October 2010 to April 2011 in 77 fantail goldfish females. Results showed that the studied reproductive parameters increased gradually from October, to attain peak in March and decreased again thereafter. Absolute fecundity ranged between 2877- 357246 eggs, GSI 7.28-19.11 and egg diameter 298-1006 micron. Regression relationships between the various studied morphometric and reproductive parameters were calculated and the importance of these results to the culturists of this commercially important ornamental fish species was discussed.